Building Assesment in Riparian Zone of Code Watershed - Wijaya Diva Darma; Nursetiawan Nursetiawan; Ibrahim Muhammad Shazril Idris (E3S Web of Conferences)
Population growth is a significant problem in the amount of land change that occurs. The Code River watershed in Yogyakarta has experienced urbanization due to the lack of land for housing, even though the Code River watershed has a vital role in community activities as the center of government, economy, tourism and history. In determining the width of the border, it adapts to morphological and demographic conditions. Satellite data processing utilizes deep learning using the Object Based Image Analysis (OBIA) method. The results obtained are the width of demographic boundaries varying from 3 m and 10 m. In the object evaluation carried out, the completeness rate is 83.5% and the quality is 69.1%. The number of buildings detected in the boundary area is 1178. The midstream area is an area with dense building conditions compared to the downstream and upstream. building use is dominated by residential buildings and MSME although there are other buildings such as hospitals, buildings, farms, schools, tourism area and factories.